Gender gaps in PISA test scores: The impact of social norms and the mother's transmission of role attitudes - Ainara González de San Román; Sara de la Rica (Institute for the Study of Labor (IZA), 2012)
The existence of gender gaps in test scores has been documented in the relevant literature for a wide range of countries. In particular, the Programme for International Student Assessment (PISA) conducted by the OECD over the past ten years reveals that on average female students underperform (outperform) males in maths (reading) test scores in most of the countries that take part in the evaluation programme. We find that differences in culture and social norms across countries and across regions within the same country are crucial determinants in understanding gender differences in PISA 2009 test scores: girls perform relatively better in both maths and reading in societies where gender equality is enhanced, and the effect varies over the distribution of scores. In addition, we find substantial evidence for the intergenerational transmission of gender role attitudes, especially from mothers to daughters, as the performance of girls - not that of boys, is better in families where the mother works outside home.
urn:nbn:de:101:1-201205026042
Keywords: C14; C33; I21; I24; J16; 330; PISA; test scores; achievement; gender differences; culture; role attitudes; intergenerational transmission; Bildungsniveau; Geschlecht; Kulturelle Identität; Soziale Norm; Frauen; Soziale Rolle; OECD-Staaten